Justification of physical intimate partner violence among married men in East Africa evidence from the recent demographic and health survey (2015–2022): a multilevel analysis - Demissie, Kaleb Assegid; Geberu, Demiss Mulatu; Teshale, Getachew; Jejaw, Melak; Tiruneh, Misganaw Guadie; Tafere, Tesfahun Zemene; Hagos, Asebe; Baffa, Lemlem Daniel (Frontiers in Sociology, 2025)
IntroductionMillions of women and girls worldwide are impacted by physical intimate partner violence. While physical intimate partner violence (IPV) among women is largely associated with the justification of IPV, little is known about men's attitude toward physical IPV. The aim of our study was to examine the factors associated with the justification of physical IPV among men in East Africa.MethodThe study used data from the male file (MR) of the most recent demographic and health survey, which was carried out in 10 East African countries. a weighted sample of 74,494 men who were either married or living with a partner as if married. Multilevel logistic regression models were used to examine the relationship between the independent variables and justification of physical IPV.ResultThe pooled prevalence justification of physical intimate partner violence in 10 east African countries was 24.17% (95% CI: 19.45–28.90). The highest prevalence of justification of physical IPV was in Uganda (35.31, 95% CI: 34.09–36.53), and the lowest prevalence of justification of physical IPV was in Malawi (8.88, 95% CI: 8.03–9.73). The multilevel analysis shows that men's age, working status, respondents' educational level, number of wives, and household wealth status, sex of head of household, age of the household head, place of residence, as well as community level poverty, and community level education were factors associated with the justification of physical intimate partner violence.ConclusionIn East Africa, about 24% of men agreed that physical IPV is justified. Reducing the justification of physical IPV requires advancing men's educational standing, men's economic status, and increased media awareness, with a focus on rural men and promoting educational and awareness campaigns at community level is needed.